ANALISIS DAMPAK KUALITAS PELAYANAN DALAM MENGUKUR TINGKAT KEPUASAN KONSUMEN PADA INDOMARET AIR HITAM 4 PEKANBARU - Aqsa, Muhammad Ali (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted to determine the effect of service quality on customer satisfaction at Indomaret Air Hitam 4 Pekanbaru. In this study, the quality of service is believed to have an effect on customer satisfaction. The research method used is a quantitative research approach, where data is obtained through questionnaires to respondents and the scale used is the Likert scale. The sampling technique in this study used the Incidental Sampling technique, because the population in this study was too large. The data analysis technique used simple linear regression test and t test. The results of this study indicate that the coefficient has a positive value of 1.102, this indicates that if the quality of service is improved it will lead to an increase in customer satisfaction. And from the results of the t test, it was obtained that the t count was 29,631 > t table 1,984, then Ha was accepted, so it can be concluded that the quality of service has a significant effect on consumer satisfaction at Indomaret Air Hitam 4 Pekanbaru